Does seed ingestion by bats enhance germination? A new meta‐analysis 15 years later. (6th May 2019) - Saldaña‐Vázquez, Romeo A.; Castaño, John Harold; Baldwin, Justin; Pérez‐Torres, Jairo
Abstract: The seed dispersal cycle forms the basis of vegetation establishment and population dynamics. Evidence shows varied results for the role of frugivorous bats, where ingestion and gut passage enhance seed germination for some plant species, but not for others. Using meta‐analysis techniques with a novel data base spanning 31 years of study, we answered the following questions: (1) does seed passage through bat digestive tracts result in higher probability of seed germination than seed pulp removal by humans? (2) Are there effects of seed origin, germination conditions, bat species, and plant species on the probability of seed germination? (3) Is there an effect of fruit bat dietary preferences on the probability of ingested seed germination? And (4) does seed ingestion by bats result in shorter germination time than seed pulp removal by humans? In general, seed passage through bat digestive tracts neither significantly increased the probability of germination nor reduced seed germination time. However, seed germination varied mainly with plant species and bat species, and fewer than 25% of plant species responded to bat gut passage in a positive or negative way. Plant species that were preferred by a species of bat were more likely to germinate after ingestion than non‐preferred plant species, in line with the core plant taxa hypothesis. These results suggest that: (1) the principal role of frugivorous bats in seed dispersal is to transport seeds away from parent plants, (2) handling of fruit by bats does not enhance or hinder seed germination, and (3) germination of the seeds of fruits consumed by bats is idiosyncratic to the bat and plant species in question.